The Morbidity of Multivariable Grey Model MGM(1,m) - Haixia Wang; Lingdi Zhao; Mingzhao Hu (International Journal of Differential Equations)
This paper proposes the morbidity of the multivariable grey prediction MGM(1,m) model. Based on the morbidity of the differential equations, properties of matrix, and Gerschgorin Panel Theorem, we analyze the factors that affect the morbidity of the multivariable grey model and give a criterion to justify the morbidity of MGM(1,m). Finally, an example is presented to illustrate the practicality of our results.